“Like a Freshman Who Didn’t Get a Freshman Orientation”: How Transfer Student Capital, Social Support, and Self-Efficacy Intertwine in the Transfer Student Experience - Cepeda, Rebecca; Buelow, Melissa T.; Jaggars, Shanna S.; Rivera, Marcos D. (Frontiers in Psychology, 2021)
Community colleges and other open-access two-year campuses provide an important pathway to higher education; however, a surprisingly small proportion of these students successfully transfer to and graduate from a bachelor’s degree-granting institution. The present study examined barriers and challenges students faced as they built their sense of self-efficacy as transfer students. We conducted interviews with 65 prospective or recent transfer students, including “internal” transfers (moving from an open-access predominantly two-year campus to their university’s flagship campus) and “external” transfers (moving from a community college to the university’s most selective campus). Our results indicate that both internal and external transfer students experienced challenges in terms of obtaining accurate information about transfer (transfer student capital, or “TSC”), but these challenges were easier to overcome for internal transfers, in part due to their social support networks. While both sets of transfer students utilized social support networks as an informal source of TSC, internal transfer students reported a more extensive social support network. Gaining accurate information about transfer and being supported by members of their social networks seemed to boost self-efficacy for transfer as well as adjustment during the post-transfer experience period. Recommendations for sending and receiving institutions are provided.